n(n+1)/2
You can see this from the following:
Let x=1+2+3+...+n
This is the same as x=n+(n-1)+...+1
x=1+2+3+...+n
x=n+(n-1)+...+1
If you add the corresponding terms on the right-hand side of the two equations together, they each equal n+1 (e.g., 1+n=n+1, 2+n-1=n+1, ..., n+1=n+1). There are n such terms. So adding the each of the left-hand sides and right-hand sides of the two equations, we get:
x+x=(n+1)+(n+1)+...+(n+1) [with n (n+1) terms on the right-hand side
2x=n*(n+1)
x=n*(n+1)/2
A more formal proof by induction is also possible:
(1) The formula works for n=1 because 1=1*2/2.
(2) Assume that it works for an integer k.
(3) Now show that given the assumption that it works for k, it must also work for k+1.
By assmuption, 1+2+3+...+k=k(k+1)/2. Adding k+1 to each side, we get:
1+2+3+...+k+(k=1)=k(k+1)/2+(k+1)=k(k+1)/2+2(k+1)/2=(k(k+1)+2(k+1))/2=((k+2)(k+1))/2=(((k+1)+1)(k+1))/2=((k+1)((k+1)+1)/2
1+2+3+4.....+100 = 101*50= 5050
(n2 + n)/2 1+2+3+4+5+n= 15+n
The sum of 5/12 and 2/3 is 1 1/12The sum of 5/12 and 2/3 is 1 1/12
500,000,500,000 is the answer.
The sum of 2/3 and 5/6 is 1 1/2.
3
Sum = 79*(79+1)/2 = 79*80/2 = 3160
3
25
if (n%2==0) sum=n/2*(n+1); else sum=(n+1)/2*n;
87
5050
41
1+2+3+4.....+100 = 101*50= 5050
The sum of -1 and -2 is -3.
The sum of 3x plus 2 and -4 plus 3 is 3x+1 if the equation is (3x+2)+(-4+3). If they are two separate questions, 3x+2 remains as itself while -4+3=-1.
81*82/2= 3321